Diseño de un prototipo de máquina fileteadora para trucha arcoíris en la finca La Victoria de la Argentina (Huila) (2020)
The main objective of this project is to design a prototype of a rainbow trout filleting machine, to be execution on the La Victoria farm in the municipality of Argentina (Huila). It is a solution that replaces the traditional manual filleting method, which generates risks in occupational safety, hygiene in terms of product handling, which translates into its poor quality, lower product price and high costs in the hands of work, which makes the business not profitable economically. To solve this problem, I propose the design of a prototype of a filleting machine, on which I have taken as a basis the theoretical guidelines and principles for the development of current fish filleting machines, including analyzes of their components and the structures that support such machines. , the static studies and calculations using the “SolidWorks” “Inventor” software for mechanical modeling in 2D and 3D and the results obtained allow us to propose the design of a prototype filleting machine, with the following characteristics